Edukasi Manajemen Keuangan Keluarga Dalam Mengatasi Kemiskinan Ekstrim Di Desa Mekar Baru - Samosir, Hasrat Efendi; Harahap, Maulana Alghofari; Wardani, Putri; Hasibuan, Ilaika Fauziah Abdi; Salsabyila, Siti Nur; Nasution, Khairani Fitriah; Divany, Adelia; Bilqish, Alifia; Diningrum, Aulia (Universitas Islam Negeri Sumatera Utara, 2024)
Poverty is a problem faced by many countries in the world, especially developing countries. One of the main goals of these countries. Indonesia is alleviating poverty and improving people's welfare. Indonesia as a developing country has implemented a national strategy to reduce extreme poverty through various alleviation programs. One of the efforts made is through family financial management education, which is carried out by the KKN 72 Group in Mekar Baru Village. This educational activity involves two main stages: preparation and social analysis, and program implementation. This education is focused on family financial management, especially through investment, with detailed explanations regarding the concept, reasons, objectives and benefits of investment, types of investment that are suitable for lower middle class economic communities, risks that may be faced, and the right time to invest. Based on the results of the activity, it was found that participants understood the importance of family financial management, this activity had the potential to help overcome extreme poverty in Mekar Baru Village, and was able to reduce the level of illegal investment fraud which was growing rapidly.